The xanthophyll cycle in green algae (chlorophyta): its role in the photosynthetic apparatus - Masojídek, J; Kopecký, J; Koblízek, M; Torzillo, G (Plant biology (Stuttgart, Germany), 2004)
Light-dependent conversion of violaxanthin to zeaxanthin, the so-called xanthophyll cycle, was shown to serve as a major, short-term light acclimation mechanism in higher plants. The role of xanthophylls in thermal dissipation of surplus excitation energy was deduced from the linear relationship between zeaxanthin formation and the magnitude of non-photochemical quenching. Unlike in higher plants, the role of the xanthophyll cycle in green algae (Chlorophyta) is ambiguous, since its contribution to energy dissipation can significantly vary among species. Here, we have studied the role of the xanthophyll cycle in the adaptation of several species of green algae (Chlorella, Scenedesmus, Haematococcus, Chlorococcum, Spongiochloris) to high irradiance. The xanthophyll cycle has been found functional in all tested organisms; however its contribution to non-photochemical quenching is not as significant as in higher plants. This conclusion is supported by three facts: (i) in green algae the content of zeaxanthin normalized per chlorophyll was significantly lower than that reported from higher plants, (ii) antheraxanthin + zeaxanthin content displayed different diel kinetics from NPQ and (iii) in green algae there was no such linear relationship between NPQ and Ax + Zx, as found in higher plants. We assume that microalgae rely on other dissipation mechanism(s), which operate along with xanthophyll cycle-dependent quenching.
Keywords: xanthofyly; chlorofyl; Light; aklimatizace; světlo; zeaxanthiny; beta Carotene; Acclimatization; fotosyntéza; Xanthophylls; Photosynthetic Reaction Center Complex Proteins; fotosyntetická reakční centra (proteinové komplexy); Zeaxanthins; beta-karoten; Photosynthesis; Temperature; Chlorophyll; teplota; Chlorophyta